Patient perception of anticoagulant treatment for stroke prevention (RE-SONANCE study). Issue 1 (24th March 2020) - Vinereanu, Dragos; Napalkov, Dmitry; Bergler-Klein, Jutta; Benczur, Bela; Ciernik, Martin; Gotcheva, Nina; Medvedchikov, Alexey; Põder, Pentti; Simic, Dragan; Skride, Andris; Tang, Wenbo; Trusz-Gluza, Maria; et al.
Abstract : Objective: We evaluated atrial fibrillation (AF) patients' perceptions of anticoagulation treatment with dabigatran or a vitamin K antagonist (VKA) for stroke prevention, according to accepted indications. Methods: The RE-SONANCE observational, prospective, multicentre, international study used the validated Perception on Anticoagulant Treatment Questionnaire (PACT-Q) to assess patients with AF already taking a VKA who were switched to dabigatran (cohort A), and newly diagnosed patients initiated on either dabigatran or a VKA (cohort B). Visit 1 (V1) was at baseline, and visit 2 (V2) and visit 3 (V3) were at 30–45 and 150–210 days after baseline, respectively. Primary outcomes were treatment satisfaction and convenience in cohort A at V2 and V3 versus baseline, and in cohort B for dabigatran and a VKA at V2 and V3. Results: The main analysis set comprised 4100 patients in cohort A and 5365 in cohort B (dabigatran: 3179; VKA: 2186). In cohort A, PACT-Q2 improved significantly (p<0.001 for all) for treatment convenience (mean change V1 vs V2=20.72; SD=21.50; V1 vs V3=24.54; SD=22.85) and treatment satisfaction (mean change V1 vs V2=17.60; SD=18.76; V1 vs V3=21.04; SD=20.24). In cohort B, mean PACT-Q2 scores at V2 and V3 were significantly higher (p<0.001 for all) for dabigatran versus a VKA for treatment convenience (V2=18.38; SE =0.51; V3=23.34; SE=0.51) and satisfaction (V2=15.88; SE=0.39; V3=19.01; SE=0.41). Conclusions: Switching to dabigatran from long-term VKA therapy or newly initiated dabigatran is associated with improved patient treatment convenience and satisfaction compared with VKA therapy.